2018
DOI: 10.1177/1759720x18776224
|View full text |Cite|
|
Sign up to set email alerts
|

The role of the JAK/STAT signal pathway in rheumatoid arthritis

Abstract: Proinflammatory cytokine activation of the Janus kinase/signal transducers and activators of transcription (JAK/STAT) signal transduction pathway is a critical event in the pathogenesis and progression of rheumatoid arthritis. Under normal conditions, JAK/STAT signaling reflects the influence of negative regulators of JAK/STAT, exemplified by the suppressor of cytokine signaling and protein inhibitor of activated STAT. However, in rheumatoid arthritis (RA) both of these regulators are dysfunctional. Thus, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(151 citation statements)
references
References 105 publications
(132 reference statements)
3
146
0
2
Order By: Relevance
“…Over the past decades, the JAK family has been regarded as an attractive drug target for the treatment of RA or other diseases 55,56 . We are excited to report that the natural compound NOT effectively acts on JAK2/3 to specifically blocks the JAK-STAT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, the JAK family has been regarded as an attractive drug target for the treatment of RA or other diseases 55,56 . We are excited to report that the natural compound NOT effectively acts on JAK2/3 to specifically blocks the JAK-STAT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient apoptosis and hyperplasia are considered to be one of the main factors in pathogenesis of RA due to JAK/STAT signaling pathway closely related to cell proliferation and apoptosis 155. Continuous activation of the JAK/STAT signaling in RA synovial joints results in higher expression level of MMP gene, increasing frequency of apoptotic chondrocytes and most prominently “apoptosis resistance” in the inflamed synovial tissues 156. Cytokines activate several signal transduction pathways such as JAK/STAT, stress‐activated/mitogen‐activated protein kinase (SAPK/MAPK), and phosphatidylinositol‐3‐kinase/Akt/mechanistic target of rapamycin (PI3K/Akt/mTOR) which regulate numerous cellular responses 157.…”
Section: Nanotherapeutics Of Ra Based On Nanodrugsmentioning
confidence: 99%
“…[155] Continuous activation of the JAK/STAT signaling in RA synovial joints results in higher expression level of MMP gene, increasing frequency of apoptotic chondrocytes and most prominently "apoptosis resistance" in the inflamed synovial tissues. [156] Cytokines activate several signal transduction pathways such as JAK/STAT, stressactivated/mitogen-activated protein kinase (SAPK/MAPK), and phosphatidylinositol-3-kinase/Akt/mechanistic target of rapamycin (PI3K/Akt/mTOR) which regulate numerous cellular responses. [157] For example, Malemud and Pearlman reported that IL-6-mediated signaling and activation of JAK3 was regulated by the binding of IL-6 to gp130.…”
Section: Jak/stat Pathways Inhibitors Therapymentioning
confidence: 99%
“…[ 47 ] Similarly, the IL‐6 binds to the type‐1 cytokine receptor activating JAK1 and JAK2 phosphorylating STAT3, and the STAT3 dimmers translocated to the nucleus stimulating the transcription of genes involved in acute‐phase immune reactions causing inflammation. [ 48 ] The inhibition of JAK family tyrosine kinase is well recognized as potential target of herbal plants used in RA. The various studies have concluded that the results based on the docking techniques have identified the plants comprising phytoconstituents like curcumin, berbamine, quercetin and salvianolic acid B as inhibitor for JAK3.…”
Section: Jak‐stat Signalling In Ramentioning
confidence: 99%